Analyzing effects of low water fords on stream stability at Fort Riley, Kansas - Malinga, Gilbert Aporu (Kansas State University, 2007)
Military maneuvers involve effectively moving soldiers and equipment across training lands, and this often involves crossing streams. Fording of streams by military vehicles poses a potential for degradation of stream habitats through change of bank angle or excess shear of stream banks and the resultant generation of excessive quantities of sediment, possibly exceeding Total Maximum Daily Loads (TMDL) limits for water quality downstream. This study examines the impact of low water fords on stability of six stream reaches at Fort Riley. Streams with constructed low water fords were mapped and classified according to Rosgen Stream Classification System (1996). Results indicate that some of these streams exhibit some level of instability, which includes bed form changes, accelerated stream bank erosion and backwater pool formation in the vicinity of stream crossings. Poorly constructed fords may act as dams disrupting the transport of sediment along the stream reaches, posing a potential shift in stream equilibrium. Another factor contributing to stream instability is sediment generated from upland areas and routed through approach roads leading to stream crossing sites. The sediment deposited into streams at these crossing locations is a water quality concern, and again poses the potential of disrupting stream equilibrium. Field observations indicate that poorly located stream crossings can alter the direction of stream flow, causing bank erosion on areas immediately below stream crossings. This demonstrates the importance of locating stream crossings on stable locations along a stream reach. Some of the stream reaches also show signs of success ional change. These stream changes have direct implications on the low water fords on Fort Riley. As a result of these stream changes, there will be need to constantly modify the designs and construction techniques of the low water fords in order to accommodate changes in stream dimensions, pattern and profile. Finally, criteria for site selection, design and construction of low water fords are discussed.
Keywords: Low Water Fords/ Stream Crossings; Sediment; Military Training; Stream Stability; Agriculture, Forestry and Wildlife (0478); Engineering, Agricultural (0539); Engineering, Environmental (0775)